IMPLEMENTATION OF FISH AUCTION PLACES RETRIBUTION POLICY IN PANGANDARAN REGENCY - Tio Agustian; Otong Husni Taufiq; Abdul Mutolib (Faculty of Social And Political Science Universitas Galuh, 2022)
This research is motivated by the implementation of policies regarding fees at fish auction sites by the Department of Marine Fisheries and Food Security, Pangandaran Regency which is still not optimal. The purpose of this study was to determine the implementation of policies regarding fees at fish auction sites by the Department of Marine Fisheries and Food Security, Pangandaran Regency. The research method used in this study is a descriptive method with a qualitative approach. This data was obtained using library research and field studies (observations, interviews, and documentation). The results of this study indicate that the implementation of the Fish Auction Place Retribution Policy by the Department of Marine Fisheries and Food Security in Pangandaran Regency is still not running optimally. It can be seen from the results of the research that the government can do this by conducting door-to-door guidance to fishermen and fish auction places, then conducting socialization with fishermen and business actors. The obstacle faced is the division of tasks and cooperation that is not what has been determined by the Department of Marine Fisheries and Food Security of Pangandaran Regency. Efforts made by the Department of Marine Affairs, Fisheries and Food Security of Pangandaran Regency to build synergy by cooperating with several cooperatives and civil service police units or Satpol PP in the process of collecting fish auction retribution so that it runs more effectively and efficiently.